JURISPRUDENCE POSITION IN THE COMMON AND CIVIL LAWS (Journal of Humanities and Social Studies, 2018)
The development of jurisprudence continues to grow in accordance with the existing laws in the society which it is not the same as the law in legal development. It is not related to the rigid nature of the law which only regulates the general nature and the process of its formation takes a long time. In practice,  the development of jurisprudence, as one of the sources of formal law,  can be distinguished into two legal systems affecting the legal world. They are namely the Continental European legal system with its Civil Law System which prioritizes "codification" in the field of law and the Anglo Saxon law with its Common Law System, which is famous for the "Precedent" system binding the judges to follow the previous judgment in deciding the same case.